A Cone-Beam Computed Tomography Evaluation of C-Shaped Canal Configuration in Maxillary Molars Among an Iranian Population - Nafiseh Nikkerdar; Mohammad Moslehi; Amin Golshah (International Journal of Dentistry)
Conclusion: The prevalence of C-shaped canals in maxillary first, second, and third molars was 1%, 7%, and 9%, respectively. C-shaped canals were more common in females, and type III other types (B-P) was the most frequent configuration in our study population.